(untitled) (Scientific journal of the Fergana State University, 2023)
The physicochemical properties of adsorbents obtained by thermal processing of stone fruit wastes were investigated. The possibility of their use for the purification of waste water from heavy metal ions in experiments with simulated waste water containing copper ions has been studied